Comparison of Nifedipine Vs. Labetalol in Preeclampsia Hypertensive Emergency in Terms of Mean Time to Reach Target Blood Pressure at a Tertiary Care Hospital - Naseem, Maryam; Shabir, Noshena; Basharat, Sundas; Ahmed, Tehniat (Indus Journal of Bioscience Research, 2025)
Background: Preeclampsia-related hypertensive emergencies represent a critical obstetric complication with potentially life-threatening maternal and fetal outcomes. Rapid pharmacologic control of blood pressure is vital to prevent progression to eclampsia and associated morbidities. Nifedipine and labetalol are commonly recommended first-line agents; however, their relative efficacy in achieving timely blood pressure control remains a subject of clinical importance. Objective: To compare the nifedipine and labetalol in preeclampsia hypertensive emergency in terms of mean time to reach target blood pressure. Study Design: Randomized controlled trial. Duration and Place of Study: This trial was conducted from January 2025 to May 2025 in the Department of Obstetrics and Gynecology, Combined Military Hospital, Muzaffarabad. Methodology: Sixty pregnant women meeting diagnostic criteria for preeclampsia hypertensive emergency were randomized into two equal groups. Group A received sublingual nifedipine (10 mg every 15 minutes, maximum five doses), while Group B was treated with intravenous labetalol in escalating doses. Blood pressure was monitored at 10-minute intervals, and the primary outcome was defined as the time taken to achieve target blood pressure of ≤140/90 mmHg. Results: Baseline characteristics including age, gestational age, parity, body mass index, admission blood pressure, and proteinuria were comparable between groups. The mean time to achieve target blood pressure was significantly lower in the nifedipine group (30.83±3.40 minutes) compared to the labetalol group (51.50±4.13 minutes) (p